1998
DOI: 10.1142/s0192415x98000038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Substance P Concentration in Acupuncture Points in Different Tissues in Dogs

Abstract: Histologically, acupuncture points show neuronal innervation. One hundred seventy-seven tissue samples of acupuncture points and control points from 4 dogs were collected. Concentrations of substance P, a neurotransmitter, in the skin, muscle and subcutis of acupuncture points and control points were measured by means of enzyme immunoassay. The determined tissue concentrations of substance P (mean +/- SEM) in acupuncture points and control points were 1.81 +/- 0.13 and 1.51 +/- 0.1 ng/g in the muscle, 3.33 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
2
16
0
2
Order By: Relevance
“…Depending on the needle's depth, a 3-fold higher concentration of substance P in the skin and subcutaneous was observed than its concentration in the muscle level. 32 This may indicate that the needle's depth evokes different intensities of stimulus or else acts over distinct segments, reaching the neural chain differently. It is important to pinpoint that as the 4 sub-systems (dermatomes, myotomes, sclerotomes, and viscerotomes) are overlapped and not coincident at the same level, 20 the needling may activate diverse sub-systems and different segments at the same time.…”
Section: Silvamentioning
confidence: 99%
“…Depending on the needle's depth, a 3-fold higher concentration of substance P in the skin and subcutaneous was observed than its concentration in the muscle level. 32 This may indicate that the needle's depth evokes different intensities of stimulus or else acts over distinct segments, reaching the neural chain differently. It is important to pinpoint that as the 4 sub-systems (dermatomes, myotomes, sclerotomes, and viscerotomes) are overlapped and not coincident at the same level, 20 the needling may activate diverse sub-systems and different segments at the same time.…”
Section: Silvamentioning
confidence: 99%
“…It has also been suggested that low impedance of acupoints on the skin may reflect the variation in anatomical concentration of nerve fibers beneath the skin and represent areas of potentially high neuronal activity (Luciani, 1978). The number of nerve bundles, nerve fibers, and nerve endings has been shown to be higher in the skin under low impedance line than those on their adjacent control areas both in human and rats (Chan et al, 1998;Zhu and Hao, 1989). The epidermis and the outer root sheath possess both neuronal nitric oxide synthase (nNOS) immunoreactivity and reduced form of nicotinamide adenine dinucleotide phosphate (NADPH) diaphorase reactivity (Dippel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Assim, alterações da mucosa da bexiga urinária e/ou da neuroquímica cerebral podem estar relacionadas à inflação neurogênica da bexiga na DTUIF idiopática (DOWERS, 2009;HOSTUTLER et al, 2005), na qual a ação de neuropeptídeos, principalmente a SP, resulta na ativação de mastócitos, levando à liberação de substâncias vasoativas como: histamina, prostaglandinas, proteases, fosfolipases, citocinas e leucotrienos, contribuindo para o processo inflamatório culminando em dor, injuria tecidual e fibrose, ou seja, no desenvolvimento das alterações histopatológicas, bem como na manifestação dos sintomas relacionados a DTUIF e à CIH (CHANG et al, 1998;HOSTUTLER et al, 2005;KRUGER et al, 2008;RECHE JR & HAGIWARA, 2001;SCOGNAMILLO-SZABÓ & BECHARA, 2001).…”
Section: A Doença Do Trato Urinário Inferior Dos Felinosunclassified
“…A SP é sintetizada na raiz dorsal ganglionar, sendo transportada axoplasmaticamente até as porções terminais dos nervos sensitivos, e sua liberação estimula diferentes atividades biológicas, como contração de musculatura lisa, vasodilatação periférica e secreção glandular, e está relacionada à transmissão nociceptiva (MERSDORF et al, 1992;SCOGNAMILLO-SZABÓ & BECHARA, 2001), apresentando papel importante na transmissão da dor e no mecanismo de ação da acupuntura (CHANG et al, 1998). A SP foi identificada nos neurônios sensitivos e nas suas respectivas terminações na raiz dorsal da medula espinal, e os segmentos lombar e sacral, que correspondem às origens das fibras nervosas aferentes e eferentes dos nervos pudendo e pélvico, responsáveis pelas micção e defecação, apresentam alta concentração de SP, sugerindo que essas funções possam ser reguladas pela SP (MERSDORF et al, 1992).…”
Section: Ciência Rural V40 N3 Mar 2010unclassified